Research on the toxicological safety of the production and operation of products made of sircogysms - Тарасевич, Віталій Іванович; Григорчук, Олександр Михайлович (Вид-во КНУТД, 2025)
Technical sulfur is increasingly used as a molten impregnation agent to modify capillary-porous construction materials, including gypsum-based products, intended for service in aggressive environments. This study evaluates the toxicological and hygienic safety of gypsum–sulfur composites produced by impregnating gypsum samples with molten sulfur. The results indicate the absence of hazardous compounds of mercury, thallium, selenium, lead, bismuth, and chromium in the investigated materials. No emissions of sulfur dioxide or hydrogen sulfide were detected at 40 °C, and no migration of inorganic compounds was observed in water or in media simulating acid rain. During impregnation at 140–150 °C, sulfuric anhydride and trace hydrogen sulfide were detected in workplace air at levels below permissible limits, corresponding to a moderately polluted (Class III) environment. Dermal tests showed a moderate irritant effect, while allergenic activity was not identified. The material is recommended for manufacturing tiles for industrial and public buildings
Keywords: technical sulphur; capillary-porous materials; gypsum materials; gypsum-sulphide composite; toxicological safety; application in industrial and public buildings; facing tiles